Uniqueness of auditory hallucinations in patients with schizophrenia and depressive disorder - Tahoora Ali; Santosh Kumar; Bhushan Chaudhary; Suprakash Chaudhury; Pankaj Kumar Verma (Industrial Psychiatry Journal)
Background: While over three-quarters of those suffering from schizophrenia and schizophrenia-like illnesses experience auditory hallucinations, 6% of individuals with depressive disorder report the same. Differentiating between auditory hallucinations in these two illnesses is important both diagnostically and prognostically. Aim: To compare the characteristics of auditory hallucinations in patients with schizophrenia and depressive disorder. Materials and Methods: For both schizophrenia and depressive disorder, 110 patients were selected from inpatients of a tertiary care psychiatric center by purposive sampling. They were assessed with a specially designed proforma containing sociodemographic information, information about clinical features, and characteristics of the Auditory Hallucination Scale. Results: Schizophrenia and depressive disorder patients were matched on age, education, occupation, and socioeconomic status. The patients with schizophrenia rated significantly higher on frequency, clarity, tone, intensity, distractibility, self-control, and distress dimensions of auditory hallucinations as compared to patients with depressive disorder. Conclusion: The characteristics of auditory hallucinations in schizophrenia differ significantly than those in depressive disorder, which bears significant transdiagnostic importance. Clinical evaluation of these differentiating characteristics of auditory hallucinations may aid in diagnostic workup in patients.